IMPACT OF REVENUE RECOGNITION (PSAK 72) ON THE FINANCIAL PERFORMANCE OF REAL ESTATE - Abdul Aziz Aji Mustiko; Yuniarti Hidayah Suyoso Putra (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
This research aims to apply revenue recognition based on PSAK 72 to the financial performance of real estate companies. The real estate sector is considered one of the sectors significantly affected by the issuance of PSAK 72, which replaced the previous standard, PSAK 44. This research analysis uses qualitative content analysis techniques and non-probability purposive sampling techniques on real estate companies listed on the Indonesia Stock Exchange that meet the criteria. Fifty-six companies become the research sample. The results show that the application of revenue recognition based on PSAK 44 makes the company's financial performance look better when compared to using PSAK 72. The settings in PSAK 72 make income from long-term contracts in companies unable to be recognized in 2020. Therefore, the revenue value in 2020 for each company will be smaller than the revenue recognized under PSAK 44.